Like mother like son? Experimental evidence on the transmission of values from parents to children - Marco Cipriani; Paola Giuliano; Olivier Jeanne (Institute for the Study of Labor (IZA), 2007)
This paper studies whether prosocial values are transmitted from parents to their children. We do so through an economic experiment, in which a group of Hispanic and African American families play a standard public goods game. The experimental data presents us with a surprising result. We find no significant correlation between the degree of cooperation of a child and that of his or her parents. Such lack of cooperation is robust across age groups, sex, family size and different estimation strategies. This contrasts with the typical assumption made by the theoretical economic literature on the inter-generational transmission of values. The absence of correlation between parents' and children's behavior, however, is consistent with part of the psychological literature, which emphasizes the importance of peer effects in the socialization process.
urn:nbn:de:101:1-2008040268
Keywords: 330; Soziale Werte; Eltern; Kinder; Sozialpsychologie; Spieltheorie